2011
DOI: 10.1371/journal.pcbi.1002160
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Compartment Model for Interneurons in the Dorsal Lateral Geniculate Nucleus

Abstract: GABAergic interneurons (INs) in the dorsal lateral geniculate nucleus (dLGN) shape the information flow from retina to cortex, presumably by controlling the number of visually evoked spikes in geniculate thalamocortical (TC) neurons, and refining their receptive field. The INs exhibit a rich variety of firing patterns: Depolarizing current injections to the soma may induce tonic firing, periodic bursting or an initial burst followed by tonic spiking, sometimes with prominent spike-time adaptation. When release… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
66
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(76 citation statements)
references
References 93 publications
5
66
0
Order By: Relevance
“…The increased I SK , in turn, delayed the induction of the next spike and hence resulted in a loss of gain (flattening) in the f-I curve (Figure 3). This finding is in line with previous modeling studies that also have highlighted the role of Ca 2+ -activated K + currents in modulating f-I curves (18,19). …”
Section: Resultssupporting
confidence: 93%
“…The increased I SK , in turn, delayed the induction of the next spike and hence resulted in a loss of gain (flattening) in the f-I curve (Figure 3). This finding is in line with previous modeling studies that also have highlighted the role of Ca 2+ -activated K + currents in modulating f-I curves (18,19). …”
Section: Resultssupporting
confidence: 93%
“…With the possible exception of the signalling molecule Ca 2+ (see e.g., [28], [29]), ion concentrations are typically assumed to be constant. The effect of ionic diffusion (due to concentration gradients) on the net electrical currents is neglected in standard cable theory, and resistivities (which in reality depend on ion concentrations) are assumed to be constant.…”
Section: Introductionmentioning
confidence: 99%
“…The currents used in the model of feed-forward interneuron, I T , I CAN , I KCa , I K , I Na , I L and I H , were identified by Zhu et al (1999) in the rat thalamus, and recently also found by Halnes et al (2011) in the mouse LGN. We used the appropriate currents from TC and PGN model cells and adjusted parameters to fit to physiological responses of feed-forward interneurons observed by Pape and McCormick (1995).…”
Section: Methodsmentioning
confidence: 78%
“…The simulated thalamic cells were based on previous physiological and modeling investigations (Huguenard and McCormick 1992; McCormick and Huguenard 1992; Destexhe et al 1994; Pape and McCormick 1995; Zhu and Uhlrich 1997; Zhu et al 1999; Halnes et al 2011) and included all identified currents (listed below in sections describing specific Cell models). All parameters of thalamic model cells were adjusted to fit their responses to injected currents to those observed in the physiological experiments mentioned above.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation